Health management gaps and EHR willingness among ethnic minority residents with rural backgrounds in Yunnan, China: a mixed-methods study - Zetian Wang; Lingling Zheng (Frontiers in Public Health, 2026)
Background Digital health monitoring and electronic health records (EHRs) are increasingly used to support chronic disease management and community-based public health services. However, their implementation in rural ethnic minority communities depends not only on technical availability, but also on residents’ service contact, perceived usefulness, digital support, and expectations of feedback. Objective This study examined health management gaps, digital health exposure, and EHR willingness among ethnic minority residents with rural community backgrounds in Yunnan Province, Southwest China. Methods: An explanatory sequential mixed-methods design was used. The quantitative phase comprised a community-based cross-sectional survey using a community-based non-probability sampling strategy combining on-site convenience recruitment with participant referral (snowball sampling). After data screening, 567 valid questionnaires were retained. Descriptive statistics and hierarchical binary logistic regression were used to examine factors associated with EHR willingness. The qualitative phase comprised semi-structured interviews with 21 residents to explain selected quantitative findings. Results Routine health management gaps were evident. Overall, 60.3% of participants reported no annual health check-up, 72.3% reported no or unclear exposure to free health check-ups in the past year, and 45.7% were unwilling to establish an EHR. In the final regression model, EHR willingness was associated with free health check-up experience in the past year (aOR = 2.14, 95% CI: 1.33–3.46), perceived importance of chronic disease management (aOR = 2.41, 95% CI: 1.64–3.54), and awareness of community-based internet-enabled chronic disease management services (aOR = 1.72, 95% CI: 1.16–2.55). Interviews suggested that EHR willingness was shaped by offline service continuity, practical barriers to using digital tools, and expectations of useful feedback after health information collection. Conclusion Digital health monitoring in rural ethnic minority communities should not be introduced as a stand-alone technical system. EHR implementation may be more acceptable when integrated with routine public health services, community-level digital support, and clear feedback mechanisms.